Evaluating Scientific Research Knowledge and Attitude Among Medical Representatives in Jordan: A Cross-sectional Survey - Mukattash, Tareq L.; Alattar, Meys; Abu-Farha, Rana K; Alsous, Mervat; Jarab, Anan S.; Darwish Elhajji, Feras W.; Mukattash, Ibrahim L. (Current Clinical Pharmacology, 2017)
Background: Pharmaceutical companies provide a broad range of different mandatory trainings to their medical representatives to keep the business running; however research related training has often been neglected by these companies. Thus, this study was developed to assess the amount of scientific research knowledge and interest among pharmacy medical representatives in Jordan. Method: A cross sectional study was conducted in Jordan in 2016. During the study period, a questionnaire was administered to 250 medical representatives working in pharmaceutical companies to evaluate their scientific research knowledge and attitudes. Results: The majority of medical representatives had positive attitudes towards clinical trials and research communication and believe that it will increase the value of their work, but a considerable number of medical representatives did not detail clinical trials on every visit and found difficulty in answering clinical trials and research related questions asked by health care professionals. Most of the medical representatives did not have a complete understanding of some basic research terminologies. Medical representatives working in multinational companies seemed to have a significantly better understanding of research and terminologies compared to local companies (P-value= 0.000). Also Medical representatives with higher educational degrees seemed to have significantly better understanding of basic research terminologies (P-value= 0.023). Conclusion: The majority of medical representatives had positive attitudes towards clinical trials and research communication and found that it will increase the value of their work, but still there is a gap in their frequency of detailing. Thus, local pharmaceutical companies need to invest more in research and clinical trials knowledge kind of training. Also, universities need to include research related courses and subject in their bachelors' program curriculum in order to make pharmacists equipped in terms of research knowledge, regardless of the career path they choose.
Keywords: Jordan